Design of Web-Based Information System for Preventive Maintenance on Forklifts with Fuzzy Logic Method at PT Henkel Footwear Speciality and Adhesives - Hendra Situmorang; Adiyanto Adiyanto; Masduki Asbari (Faculty of Science and Technology University of Pramita Indonesia, 2022)
Waste in the aspect of forklift maintenance often occurs due to poor forklift repair planning. The design of information systems for preventive service maintenance and forklift spare parts is made using the PHP programming language and MySQL database as well as a Web application that aims to reduce operator negligence and forklift mechanics who do not perform routine checks on forklifts and increase the reliability of forklift engines. This study uses object-oriented analysis and design methods, starting from the analysis of the current system using UML, elicitation of system requirements, and the description of the proposed system using UML. The method of analysis is carried out by conducting direct observations in the company, documentation by studying existing documents, research on problems, and interviews with related parties in the company. The conclusion that can be drawn by the author is that the current system is not effective and efficient so engine damage often occurs resulting in delays in support for forklift services and waste of forklift engine repair costs. For this reason, the author advises the maintenance division of PT Henkel Footwear Specialty And Adhesives to use a Web-based preventive maintenance planning system, by utilizing Web application media.